Elevated Lipoprotein(a) prevalence and association with family history of premature cardiovascular disease in general population with moderate cardiovascular risk and increased LDL cholesterol. (October 2022) - Gulayin, Pablo E.; Lozada, Alfredo; Schreier, Laura; Gutierrez, Laura; López, Graciela; Poggio, Rosana; Mores, Nora; Ponzo, Jacqueline; Calandrelli, Matías; Lanas, Fernando; Irazola, Vilma
Abstract: Background: Elevated Lipoprotein(a) [Lp(a)] is independently associated with increased cardiovascular disease (CVD) risk. There are discrepancies regarding its epidemiology due to great variability in different populations. This study aimed to evaluate the prevalence of elevated Lp(a) in people with moderate CVD risk and increased LDL-c and to determine the association between family history of premature CVD and elevated Lp(a). Methods: Random subjects from the CESCAS population-based study of people with moderate CVD risk (Framingham score 10–20 %) and LDL-c ≥ 130 mg/dL, were selected to evaluate Lp(a) by immunoturbidimetry independent of the Isoforms variability. The association between family history of premature CVD and elevated Lp(a) was evaluated using multivariate logistic regression models. Elevated Lp(a) was defined as Lp(a) ​​≥ 125 nmol/L. Results: Lp(a) was evaluated in 484 samples; men = 39.5 %, median age = 57 years (Q1-Q3: 50–63), mean CVD risk = 14.4 % (SE: 0.2), family history of premature CVD = 11.2 %, Lp(a) median of 21 nmol/L (Q1-Q3: 9–42 nmol/L), high Lp(a) = 6.1 % (95 % CI = 3.8–9.6). Association between family history of premature CVD and elevated Lp(a) in total population: OR 1.31 (95 % CI = 0.4, 4.2) p = 0.642; in subgroup of people with LDL-c ≥ 160 mg%, OR 4.24 (95 % CI = 1.2, 15.1) p = 0.026. Conclusions: In general population with moderate CVD risk and elevated LDL-c from the Southern Cone of Latin America, less than one over ten people had elevated Lp(a). Family history of premature CVD was significantly associated with the presence of elevated Lp(a) in people with LDL-c ≥ 160 mg/dL.